Development and acceptability of a decision aid for chronic insomnia considering discontinuation of benzodiazepine hypnotics. Issue 1 (22nd November 2021) - Aoki, Yumi; Takaesu, Yoshikazu; Suzuki, Masahiro; Okajima, Isa; Takeshima, Masahiro; Shimura, Akiyoshi; Utsumi, Tomohiro; Kotorii, Nozomu; Yamashita, Hidehisa; Kuriyama, Kenichi; Watanabe, Norio; Mishima, Kazuo
Abstract: Aim: To describe the development and acceptability of a decision aid (DA) for chronic insomnia considering discontinuation of benzodiazepine (BZD) and benzodiazepine receptor agonist (BZRA) hypnotics, and if discontinuing, tapering with or without cognitive behavioral therapy for insomnia (CBT‐I). Methods: We reviewed relevant literature describing chronic insomnia to identify options. We used the results of the systematic review and meta‐analysis conducted previously to determine the related outcomes of two options: discontinuation of BZD/BZRA hypnotics by gradual tapering alone and discontinuation of BZD/BZRA hypnotics by gradual tapering with CBT‐I. We then developed a prototype of DA following the International Patient Decision Aid Standards. A mixed methods survey was conducted to assess the acceptability among patients and healthcare providers. Results: The prototype consisted of a description of insomnia, options of continuing or discontinuing BZD/BRZA hypnotics (if discontinuing, the options of tapering hypnotics with or without CBT‐I), pros and cons of each option, and a value clarification exercise. Patients (n = 24) reported that the DA had acceptable language (79%), adequate information (71%), and well‐balanced presentation (91%). Healthcare providers (n = 20) also provided favorable feedback. Conclusion: We developed a DA for chronic insomnia considering discontinuation of BZD/BRZA hypnotics, which was acceptable for stakeholders. The developed DA was designed to support patients and healthcare providers to make a decision about whether to discontinue BZD/BRZA hypnotics.